2021
DOI: 10.1038/s41467-021-24786-2
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the role of group-based morality in extreme behavioral expressions of prejudice

Abstract: Understanding motivations underlying acts of hatred are essential for developing strategies to prevent such extreme behavioral expressions of prejudice (EBEPs) against marginalized groups. In this work, we investigate the motivations underlying EBEPs as a function of moral values. Specifically, we propose EBEPs may often be best understood as morally motivated behaviors grounded in people’s moral values and perceptions of moral violations. As evidence, we report five studies that integrate spatial modeling and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 59 publications
2
37
0
Order By: Relevance
“…Future research can extend other MFT-based measurement tools. Among others, the Moral Foundations Dictionary (Graham et al, 2009), Moral Foundations Dictionary 2.0 (Frimer et al, 2019), Moral Foundations Vignettes (Clifford et al, 2015), Moral Foundations Sacredness Scale , Moral Foundations Twitter Corpus (Hoover et al, 2020), MapYourMorals (Hoover et al, 2021), the Socio-Moral Image Database (Crone et al, 2018), andMoral andAffective Film Set (McCurrie et al, 2018) can be updated in accordance with the new findings and refinements reported here, further generating testable hypotheses about human morality in different contexts which can be measured using different methodologies.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Future research can extend other MFT-based measurement tools. Among others, the Moral Foundations Dictionary (Graham et al, 2009), Moral Foundations Dictionary 2.0 (Frimer et al, 2019), Moral Foundations Vignettes (Clifford et al, 2015), Moral Foundations Sacredness Scale , Moral Foundations Twitter Corpus (Hoover et al, 2020), MapYourMorals (Hoover et al, 2021), the Socio-Moral Image Database (Crone et al, 2018), andMoral andAffective Film Set (McCurrie et al, 2018) can be updated in accordance with the new findings and refinements reported here, further generating testable hypotheses about human morality in different contexts which can be measured using different methodologies.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…We used the estimates of county-level distribution of moral values provided by Hoover et al (2021). These authors relied on data from the crowd-sourcing website www.YourMorals.org, which is an online platform for collecting a wide range of psychological data, including moral values.…”
Section: Endorsement Of Moral Valuesmentioning
confidence: 99%
“…The multilevel model also included a hierarchical auto-regressive prior (Riebler et al, 2016) that, under the presence of spatial autocorrelation, induces local spatial smoothing between proximate counties (Hanretty et al, 2016;Hoover & Dehghani, 2019). To validate the county-level estimates of moral concerns, Hoover et al (2021) analyzed the relation between 8 Further details and example items are provided in the supplemental materials. Wang et al, 2015).…”
Section: Hoover Et Al (2021) Used Multilevel Regression and Synthetic...mentioning
confidence: 99%
“…Previous linguistic and computer science studies have analyzed large volumes of textual data to develop moral dictionaries (Araque, Gatti, and Kalimeri 2020;Hoover et al 2021) and examined the types of moral values represented in social media users' discussions (Grover et al 2019). In addition, scholars have investigated how individual characteristics (especially political predisposition) affect the endorsement of each moral value (Graham, Haidt, and Nosek 2009;Haidt and Graham 2007).…”
Section: Moral Values In Online Discussionmentioning
confidence: 99%